The effect of using the scientific approach through concept understanding and critical thinking in science - Syarifuddin Syarifuddin (Jurnal Prima Edukasia, 2018)
This research aimed to find out: (1) the effect of scientific approach through concept understanding in science, (2) the effect of scientific approach through critical thinking in science, and (3) the effect of scientific approach through concept understanding and critical thinking in science. The research was a quasi experimental research using pretest-posttest control group design. The population of the research was the fifth grade school elementary students in the first cluster of Palakka Bone amounted of 125 students. Technique of collecting sample was cluster random sampling which was 71 students. Data were analyzed with independent sample t-tes dan MANOVA test. The research findings showed: (1) There is a significant positive effect of scientific approach through concept understanding in science, the result obtained 0.003, (2) There is a significant positive effect of scientific approach through critical thinking in science; the result obtained 0.000, (3) there is a significant positive effect of scientific approach through concept understanding and critical thinking; the result obtained 0.000. In conclusion, the scientific approach is effective to use in science class in improving students’ concept understanding and critical thinking.